2015
DOI: 10.3390/ijerph120605833
|View full text |Cite
|
Sign up to set email alerts
|

Building-Related Symptoms among Office Employees Associated with Indoor Carbon Dioxide and Total Volatile Organic Compounds

Abstract: This study investigated whether sick building syndrome (SBS) complaints among office workers were associated with the indoor air quality. With informed consent, 417 employees in 87 office rooms of eight high-rise buildings completed a self-reported questionnaire for symptoms experienced at work during the past month. Carbon dioxide (CO2), temperature, humidity and total volatile organic compounds (TVOCs) in each office were simultaneously measured for eight office hours using portable monitors. Time-averaged w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 28 publications
4
60
1
2
Order By: Relevance
“…The indoor concentration of carbon dioxide elevated with increasing crowding levels and associated with dry throat, tiredness, and dizziness 26. The crowding levels at home were associated with cough and phlegm among children 3.…”
Section: Discussionmentioning
confidence: 95%
“…The indoor concentration of carbon dioxide elevated with increasing crowding levels and associated with dry throat, tiredness, and dizziness 26. The crowding levels at home were associated with cough and phlegm among children 3.…”
Section: Discussionmentioning
confidence: 95%
“…One study from Dalian, China, found positive associations between 1,1,1-trichloroethane, xylene, butanol, methyl isobutyl ketone, and styrene concentrations in homes and current SBS (Guo et al, 2013). Another study from Taiwan found associations between TVOC and upper respiratory symptoms, dry throat and mucosal irritation (Lu et al, 2015). One study found positive associations between levels of ethylbenzene, trichloroethylene, xylene and TVOC in population-based samples of homes in France (Billonnet et al, 2011).…”
Section: Introductionmentioning
confidence: 97%
“…The EPA requires that the indoor air quality (IAQ) of rapid transit systems to comply with the stipulated standards for CO, CO 2 , and HCHO [5]. Previous studies have associated poor indoor air quality with building-related symptoms and oxidative stress [6,7,8,9,10,11,12,13,14]. The accumulation of indoor CO 2 , HCHO, TVOCs, O 3 , PM 10 , bacteria and fungal contamination significantly increases the risks of sick building syndrome (SBS) [6,7,8,9,10,11], and high urinary 8-hydroxydeoxyguanosine (8-OHdG) levels [12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have associated poor indoor air quality with building-related symptoms and oxidative stress [6,7,8,9,10,11,12,13,14]. The accumulation of indoor CO 2 , HCHO, TVOCs, O 3 , PM 10 , bacteria and fungal contamination significantly increases the risks of sick building syndrome (SBS) [6,7,8,9,10,11], and high urinary 8-hydroxydeoxyguanosine (8-OHdG) levels [12,13,14]. Urinary 8-OHdG is considered as a biomarker for oxidative stress and has been significantly associated with building-related complaints in office workers [14,15], the exposure to polyaromatic hydrocarbons in traffic conductors and Chinese military cooks [16,17] as well as the exposure of PM 10 and PM 2.5 in bus drivers [18].…”
Section: Introductionmentioning
confidence: 99%